The mass-hierarchy and CP-violation discovery reach of the LBNO long-baseline neutrino experiment - Collaboration, LAGUNALBNO; Agarwalla, S; Agostino, L; Aittola, M; Alekou, A; Andrieu, B; Angus, D; Antoniou, F; Ariga, A; Ariga, T; Asfandiyarov, R; Autiero, D; et al. (2013)
The next generation neutrino observatory proposed by the LBNO collaboration will address fundamental questions in particle and astroparticle physics. The experiment consists of a far detector, in its first stage a 20 kt LAr double phase TPC and a magnetised iron calorimeter, situated at 2300 km from CERN and a near detector based on a high-pressure argon gas TPC. The long baseline provides a unique opportunity to study neutrino flavour oscillations over their 1st and 2nd oscillation maxima exploring the $L/E$ behaviour, and distinguishing effects arising from $δ_{CP}$ and matter. In this paper we have reevaluated the physics potential of this setup for determining the mass hierarchy (MH) and discovering CP-violation (CPV), using a conventional neutrino beam from the CERN SPS with a power of 750 kW. We use conservative assumptions on the knowledge of oscillation parameter priors and systematic uncertainties. The impact of each systematic error and the precision of oscillation prior is shown. We demonstrate that the first stage of LBNO can determine unambiguously the MH to $>5σ$C.L. over the whole phase space. We show that the statistical treatment of the experiment is of very high importance, resulting in the conclusion that LBNO has $\sim$ 100% probability to determine the MH in at most 4-5 years of running. Since the knowledge of MH is indispensable to extract $δ_{CP}$ from the data, the first LBNO phase can convincingly give evidence for CPV on the $3σ$C.L. using today's knowledge on oscillation parameters and realistic assumptions on the systematic uncertainties.